(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The Covid-19 pandemic has made the urgency of digital healthcare in Italy even more clear. In this perspective, the contribution examines the Electronic Health File and the Electronic Medical Record, as documentation that can help save on healthcare costs and more effectively protect people’s health. However, this raises the issue of the protection of personal data and notably of the right to informational self-determination in its balance with the other rights here involved.